Coastal biodiversity and pollution: a continuous conflict - Ismail, Ahmad (Universiti Putra Malaysia Press, 2011)

(untitled)
Looking at the trend of the country’s development and international concern on biodiversity in Malaysia, the government has developed a policy on conservation, biodiversity and many other policies related to the environment and biodiversity.Despite many policies, laws and regulations and commitment of many agencies on environmental protection and conservation, issues on biodiversity, conservation and protection are continuously highlighted. The demands for agriculture, industries, urbanisation and road networking have sacrificed the habitats for wildlife. The lack of expertise and public awareness on wildlife ecology and conservation caused the local authorities and developers to neglect planning for wildlife and habitat protection when designing the developments of the urban, industrial and residential areas. Many examples of habitat loss, habitat fragmentation, migration routes obstruction, poaching and habitat contamination have occurred. Great pressures can be observed on coastal wildlife. Hazardous chemicals in coastal environment in Malaysia have shown some elevation especially in specific areas. Realising that continuous developments and human activities can cause the elevation of hazardous chemicals in the coastal environment, a monitoring system is needed. In order to do this, bio-monitoring agents need to be identified and tested. From the long studies that I have conducted, many bio-monitoring agents have been proposed. Many of them are intertidal molluscs. However, more detailed studies on their biology and ecology are required. From these long term monitoring activities that were carried out, the Department of Biology, UPM has produced the most data with similar sampling methods, analysis and procedures in the literature on level and ecotoxicology of heavy metals in Malaysia. Perhaps the data produced can become guidelines for heavy metal levels in coastal marine ecosystems in Malaysia. Since heavy metals are important hazardous chemicals that can cause toxic effects, monitoring and research related to establishing bio-indicators, bio-monitors and testing organisms need to be continuously enhanced. The results of understanding the biology, ecology and ecotoxicology of heavy metals on the potential bio-indicators will enable a specific bio-indicator to be suggested for a specific micro-habitat. Establishing a specific bio-indicator for a specific micro-habitat could support the idea of conservation of organisms at all levels from chemical contamination. This innovation can later aid hazardous chemical management in coastal environment and help to reduce the conflict between coastal wildlife conservation and pollution.